Effectiveness of home or hospital initiation of treatment at diagnosis for children with type 1 diabetes (DECIDE trial): a multicentre individually randomised controlled trial. Issue 12 (3rd December 2019) - Gregory, John W; Townson, Julia; Channon, Sue; Cohen, David; Longo, Mirella; Davies, Justin; Harman, Nicola; Hood, Kerenza; Pickles, Timothy; Playle, Rebecca; Randell, Tabitha; Robling, Michael; et al.
Abstract : Objective: To determine whether, in children with newly diagnosed type 1 diabetes who were not acutely unwell, management at home for initiation of insulin treatment and education of the child and family, would result in improved clinical and psychological outcomes at 2 years postdiagnosis. Design: A multicentre randomised controlled trial (January 2008/October 2013). Setting: Eight paediatric diabetes centres in England, Wales and Northern Ireland. Participants: 203 clinically well children aged under 17 years, with newly diagnosed type 1 diabetes and their carers. Intervention: Management of the initiation period from diagnosis at home, for a minimum of 3 days, to include at least six supervised injections and delivery of pragmatic educational care. Main outcome measures: Primary outcome was glycosylated haemoglobin (HbA1c) concentration at 24 months postdiagnosis. Secondary outcomes included coping, anxiety, quality of life and use of NHS resources. Results: 203 children, newly diagnosed, were randomised to commence management at home (n=101) or in hospital (n=102). At the 24 month primary end point, there was one withdrawal and a follow-up rate of 194/202 (96%). Mean HbA1c in the home treatment arm was 72.1 mmol/mol and in the hospital treated arm 72.6 mmol/mol. There was a negligible difference between the mean HbA1c levels in the two arms adjusted for baseline (1.01, 95% CI 0.93 to 1.09). There were mostly no differences in secondary outcomes at 24 months, apart from better child self-esteem in the home-arm. No home-arm children were admitted to hospital during initiation and there were no adverse events at that time. The number of investigations was higher in hospital patients during the follow-up period. There were no differences in insulin regimens between the two arms. Conclusions: There is no evidence of a difference between home-based and hospital-based initiation of care in children newly diagnosed with type 1 diabetes across relevant outcomes. Trial registration number: ISRCTN78114042 .